2019
DOI: 10.1021/acs.inorgchem.9b00668
|View full text |Cite
|
Sign up to set email alerts
|

UV–Vis Absorption Spectroscopy of Polonium(IV) Chloride Complexes: An Electronic Structure Theory Study

Abstract: Prepared for Inorg. Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(40 citation statements)
references
References 51 publications
(95 reference statements)
5
34
0
Order By: Relevance
“…When Though it is obvious that the presence of the hydrogen atoms of the water ligands may lower the symmetry, it is actually interesting to note that in some of the cases (n = 4, 5 and 7) quite different structures were obtained. Concerning more specifically the PoCl 4 complex, Stoïanov et al reported in their article 25 a C 2v SPG for the gas-phase structure, with one set of bonds being slightly longer than the other. In fact, we found with our level of theory that the gas phase C 2v structure is only 1.6 kcal mol −1 higher in energy than the T d one, meaning that both are technically possible.…”
Section: Electronic Structure Theory Calculationsmentioning
confidence: 99%
See 3 more Smart Citations
“…When Though it is obvious that the presence of the hydrogen atoms of the water ligands may lower the symmetry, it is actually interesting to note that in some of the cases (n = 4, 5 and 7) quite different structures were obtained. Concerning more specifically the PoCl 4 complex, Stoïanov et al reported in their article 25 a C 2v SPG for the gas-phase structure, with one set of bonds being slightly longer than the other. In fact, we found with our level of theory that the gas phase C 2v structure is only 1.6 kcal mol −1 higher in energy than the T d one, meaning that both are technically possible.…”
Section: Electronic Structure Theory Calculationsmentioning
confidence: 99%
“…Note that their first ionization potential value was in good accord with the early value of Charles 10 , and proved to be also in good accord with the yet to come new experimental values derived from two independent experiments 23,24 . In 2019, Stoïanov et al revisited from theory the UV-Vis absorption spectra of polonium chloride complexes 25 . The same year, chalcogen bonding with polonium was examined by Zierkiewicz et al 26 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To aid in the interpretation of BrC light absorption, computational chemistry approaches using time-dependent density functional theory (TD-DFT) can be useful to evaluate the light absorption properties of potential BrC chromophores when authentic standards are not available. TD-DFT is a widely used ab initio approach for computing electronic spectra. The DFT component of TD-DFT computes the electronic structures of atoms, molecules, and solids at ground state, while the TD component accounts for the electronically excited-states of matter when interacting with light . Numerous studies have used TD-DFT to examine optical properties of organic and inorganic dyes in industrial applications such as dye-sensitized solar cells, , textile tinting, and photosensitizers …”
Section: Introductionmentioning
confidence: 99%